(untitled) (KYAMC Journal, 2021)
Background: Homicide is the significant issues of major public health crisis in relation to health and safety of all individuals. The number of homicide is increasing in Bangladesh at alarming rate day by day. Objectives:Considering this context, we aimed to study and explore the demography of homicidal deaths occurred at Rajshahi districtin 2020. Materials and methods: The statistics presented here isbased on the post-mortem of the dead bodies that were submitted from different police station in the Department of Forensic Medicine & Toxicology (DFMT) at Rajshahi Medical College. This present data based on the observed mark which might be analogous with corresponding manner of homicide. Results: A total 37 homicides were occurred in January 2020 to December 2020. Among them, 59% were male and 41% were female. Almost 50% victims were between 16 and 30 years old. Maximum of the male victims were farmer in profession, whereas all of the females were house wife. Surprisingly, 24% cases were from area of Charghat police station. Conclusion: The overall situation suggests taking proper action that may decrease the homicidal deaths. KYAMC Journal. 2021;12(3): 138-141